Does Participation in Home-delivered Meals Programs Improve Outcomes for Older Adults?: Results of a Systematic Review - Campbell, Anthony D. (J Nutr Gerontol Geriatr, 2015)
Participation in home-delivered meals programs may contribute to the health and independence of older adults living in the community, especially those who are food insecure or those who are making transitions from acute, subacute, and chronic care settings to the home. The purpose of this study was to conduct a comprehensive and systematic review of ALL studies related to home-delivered meals in order to shed light on the state of the science. A complete review of articles appearing in PubMed using the Keyword “Meal” was conducted; and titles, abstracts, and full-texts were screened for relevance. Included in this review are 80 articles. Most studies are descriptive and do not report on outcomes. Frequently reported outcomes included nutritional status based upon self-reported dietary intake. Additionally, most studies included in this review are cross-sectional, have a small sample size, and/or are limited to a particular setting or participant population. More rigorous research is needed to: 1) gain insight into why so few eligible older adults access home-delivered meals programs, 2) support expansion of home-delivered meals to all eligible older adults, 3) better identify what home-delivered meals models alone and in combination with other services works best and for whom, and 4) better target home-delivered meals programs where and when resources are scarce.